Reproducibility of cerebral artery Doppler measurements. Issue 7 (July 1990) - Moorthy, B; Colditz, P R; Ives, K N; Rees, D G; van't Hoff, W G; Hope, P L
Abstract : Intraobserver and interobserver variability were calculated for the measurement of cerebral artery pulsatility indices by five observers who made two recordings on each of 12 stable preterm infants. Variations in pulsatility indices of up to 0.21 were found; no measurement was below 0.55.